Aigeira 3. Forschungen im Bereich des Theaters 2011 bis 2018 (2022)
The theater terrace of Aigeira is one of the most interesting building ensembles of the Hellenistic period in the Peloponnese. Its investigation is a main focus of the long-standing activities of the Austrian Archaeological Institute in Aigeira. The volume "Aigeira 3" presents a summary of the theater area, and provides insights into the earlier excavations by Wilhelm Alzinger as well as new results from the research carried out under the direction of the editor in this area.